Morphological and genetic characterisation of Sarcocystis halieti from the great cormorant (Phalacrocorax carbo) - Prakas, Petras; Butkauskas, Dalius; Švažas, Saulius; Stanevičius, Vitas (Parasitology research (1987), 2018)
Having examined 19 great cormorants ( Phalacrocorax carbo ) hunted in Lithuania, sarcocysts were found in the muscles of two birds. Sarcocysts detected were examined using light microscopy (LM), transmission electron microscopy (TEM), and 18S rDNA, 28S rDNA, ITS1, cox1 , and rpoB sequence comparison. Based on the molecular analysis, mainly of the ITS1 region, sarcocysts were identified as Sarcocystis halieti . This is the first Sarcocystis species characterised in the great cormorant. Under the LM sarcocysts were ribbon-shaped, very long and thin (the largest fragment found amounted to 6.5 × 0.1 mm) with a smooth and thin (up to 1.2 μm) cyst wall. Banana-shaped bradyzoites were 7.2 × 1.9 (6.3–8.2 × 1.4–2.4) μm. Under TEM, the cyst wall was wavy, 0.8- to 1.2-μm thick. The comparison of 12 species demonstrated cox1 and rpoB to be unsuitable for the identification of Sarcocystis spp. using birds as intermediate hosts.